Pengaruh Hubungan Kerja Kemanusiaan Terhadap Proses Pengambilan Keputusan (Satu studi pada Kantor Kecamatan malalayang Manado) - Raranta, Deky Bernad; Posumah, Jhonny Hanny; Tampi, Gustaf (JURNAL ADMINISTRASI PUBLIK, 2015)
As it known that human factors in administration (including management and organization in the dynamic sense) holds a very important and decisive. The most important and decisive, because other than humans have feelings and ratio as being the noblest of God’s creation, is also a determinant factor, because of the "elements" of the site on the dimilki organization, such as: money, machine, material, method of work, time and other riches that can benefit your organization The activity of human relations, organization leaders trying to solve problems in work situations and issues that impinge on his subordinate individually, so that way, they can be excited towards more effective in an attempt to improve morale in the help command in the decision-making process. Further more, Maier said that with the approach of the huma relation, can be organised for eliminating obstacles obstacles of communication, prevent misjudgments and develop constructive facet of human traits The issue of decision-making at the time now this joyous attention from various parties, both from among the leaders of the Government and the company, as well as from scholars, the export and the students from various branches of science. Has been the fact that the activities carried out within each organization, intended to achieve the objectives of the Organization in question. And you want is all of the activity or the activity can run smoothly and objectives can be achieved with effective and efficient. But often occurred obstacles in carrying out activities. This is a problem that should be solved by the leadership of the organization. In the context of this decision as this develop from on leadership, a role of sagat holding a decisive in maintaining the continuity of the activities of the Organization in order to not occur stagasi (halt) Key Words: Work, Humanitarian Relations, Decision Makin